Could hematologic parameters be useful biomarkers for the diagnosis of endometriosis? - (:unkn) unknown (COMENIUS UNIV, 2019)
OBJECTIVES: The objective of this study was to evaluate the diagnostic value of the neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), and mean platelet volume (MPV) in patients with endometriosis as compared with healthy controls. BACKGROUND: Currently, no non-invasive diagnostic test of endometriosis has been implemented in clinical practice. METHODS: A total of 121 women with endometriosis and 136 controls participated in this retrospective study. The extent of the disease in the patients with endometriosis was determined using the American Society of Reproductive Medicine revised classification. Sensitivities and specificities of NLR, LMR and MPV were evaluated by receiver-operating characteristic (ROC) analysis. RESULTS: Patients with endometriosis had higher neutrophil counts, white blood cell (WBC) levels, NLR, MPV, and lower lymphocyte count and LMR than the control group. The cut-off values were found to be 1.6 for NLR at 87.6 % sensitivity and 44.8 % specificity and 8 for MPV at 75.2 % sensitivity and 68.4 % specficity. For LMR, the cut-off value was 5.6 with 66.1 % sensitivity, 50 % specificity. Patients with stages III or IV had significantly lower MPV (p = 0.039) and LMR levels (p = 0.016) than patients with stages I or II. CONCLUSION: NLR, LMR, and MPV may be used to distinguish patients with endometriosis from controls.
Keywords: CA-125; endometriosis; lymphocyte-to-monocyte ratio; mean platelet volume; neutrophil-to-lymphocyte ratio; MEAN PLATELET VOLUME; TO-LYMPHOCYTE RATIO; NEUTROPHIL; CA-125; ASSOCIATION; CURVES; AREAS; WOMEN; ROC